Use of Sulphuric Acid Paste in Resin Tapping of Chir Pine - Verma, V. P. S. (Indian Forester, 1971)
The paper deals with the use of sulphuric acid paste (with kaolin) for resin tapping. It is observed that although the absolute yield of resin from a channel does not increase but the yield in terms of freshenings increases, resulting in higher productivity per labour. The freshening height of 12 mm is found to be more favourable to resin yield than the usual freshening height. There appears to be seasonal variation in the effect of sulphuric acid on the yield of resin.